(untitled) (Our Nature, 2021)
Studies on fish community structure along altitudinal gradients of rivers are lacking in Nepal. This study was carried out to gauge the fish diversity and composition along elevational gradient in Ratuwa River. The altitudinal gradient varies between 70 m to 1300 m. Fish samples were collected based on habitat representativeness from April (spring) 10-18, July (summer) 10-18, October (autumn) 10-18, 2020 and January (winter) 10-18, 2021. A total of 3447 specimens representing 4 orders, 14 families and 36 species were identified. Both fish diversity and abundance of studied ichthyofauna vary with altitudinal gradient. The present study affirmed that fish species of Opsarius bendelisis, Schistura multifasciatus, Garra annandalei, Brachydanio rerio, Aspidoparia morar, and Schistura scaturigina are the major contributory species (>1%) for both space and time spectrums. Fish community structure testing for both to space and time showed significant difference in spatial spectrum (R=0.72, P<0.01) but no significant difference in temporal variation (R=-0.034, P>0.05). The present results hinted that fish assemblage structure varied significantly from low to high elevations, altitude, water temperature, water velocity, dissolved oxygen and pH was found as major influential factors (P<0.05) for species distribution.